MAKNA FILOSOFI MOTIF KAIN TENUN SONGKE DI DESA PONNG LENGOR KECAMATAN RAHONG UTARA KABUPATEN MANGGARAI NUSA TENGGARA TIMUR - Teklasani Juita; Ni Luh Putu Tejawati (Widyadari : Jurnal Pendidikan, 2022)
This study aims to determine (1) the forms of Songke Manggarai woven fabric motifs; (2) Factors influencing the development of Songke Manggarai woven fabric motifs; (3) The philosophical meaning of Songke woven fabric motifs. The theory used in this research is symbol theory, consumer culture theory and semiotic theory. In an effort to obtain data, the method of determining informants, data collection methods, and data processing methods is used. This study concludes that (1) the Songke Manggarai woven motifs include the wela runu motif, the ranggong motif, the wela kaweng motif, the ntala motif, the su'i motif, the seat motif (2) The development of the Songke woven fabric motif in Pong Lengor Village, North Rahong District, Manggarai is influenced by creativity factors, economic factors, consumer factors, external cultural factors, and function diversification factors (3) The Wela Runu motif implies that every life in this world must have benefits. The Ranggong motif is a symbol of honesty and hard work. The wela kaweng motif means the relationship between humans and the natural surroundings. The su'i motif (lines) has the meaning that life grows and develops.